JKN and Maternal Mortality Phenomenon at the Banyuwangi Referral Hospital, Indonesia - Al Farizi, Sofia; Katmawanti, Septa; Nuari Harmawan, Bagus (KnE Life Sciences, 2021)
Maternal mortality is a persisting problem in Indonesia. JKN can realize universal health coverage so that the service quality and its utilization can be improved. Maternal mortality in the referral hospital of Banyuwangi was stagnant during the JKN implementation. This study was a comparative analysis of the maternal mortality characteristics before and during the implementation of JKN in Banyuwangi. The study used mixed methods with sequential explanatory design. The study began with a quantitative method and was confirmed in depth by qualitative research. The study was conducted at four secondary hospitals, joined by BPJS Kesehatan. In the quantitative research, the characteristics analysed were the incidence of maternal death, cause of death, time of death, and period of death. Results showed that the proportion of maternal mortality increased after the JKN implementation [from 0.19% to 0.25%] PR = 1.31. Also, patients who died of uterine rupture and pre-eclampsia increased during the JKN implementation – from 15.39% to 18.75%, PR = 1.22 and from 7.69% to 25%, PR = 3.25, respectively. Death time < 48 hr and puerperal death also increased during the JKN implementation – from 61.5 % to 68.75%, PR 1.12 and 46.15% to 53.34%, PR = 1.15, respectively. The tiered referral and non-massive early detection affected the increase in maternal mortality. Many factors contributed to the increase in the proportion of maternal mortality characteristics at the Banyuwangi referral hospital. However, several policies of JKN need to be improved to be more effective in reducing maternal mortality. Keywords: maternal mortality, health insurance, delay in referral, early detection